2012
DOI: 10.3390/molecules17032796
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Pithecellobium Jiringa Ethanol Extract against Ethanol-Induced Gastric Mucosal Injuries in Sprague-Dawley Rats

Abstract: Current anti-gastric ulcer agents have side effects, despite the progression and expansion of advances in treatment. This study aimed to investigate the gastroprotective mechanisms of Pithecellobium jiringa ethanol extract against ethanol-induced gastric mucosal ulcers in rats. For this purpose, Sprague Dawley rats were randomly divided into five groups: Group 1 (normal control) rats were orally administered with vehicle (carboxymethyl cellulose), Group 2 (ulcer control) rats were also orally administered with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 26 publications
4
17
0
1
Order By: Relevance
“…These findings are consistent with observations from other studies [7, 32]. Therefore, the elevation of SOD and GPx enzymatic activities leads to increased scavenging of superoxides, hydrogen peroxide, hydroxyl and lipid peroxyl radicals, resulting in a reduction in tissue damage [9, 49].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with observations from other studies [7, 32]. Therefore, the elevation of SOD and GPx enzymatic activities leads to increased scavenging of superoxides, hydrogen peroxide, hydroxyl and lipid peroxyl radicals, resulting in a reduction in tissue damage [9, 49].…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with the results from other studies [20, 46]. Up-regulation of HSP70 protein in the stomach wall mucosa in animals pre-fed with C. barometz hair extract may stop the initiation of damage to the gastric epithelium upon exposure to absolute alcohol [23, 32]. The HSP70 protein protected mitochondria and delayed a stress-induced apoptotic programmer [47].…”
Section: Discussionsupporting
confidence: 90%
“…Activation and infiltration of neutrophils appear to be involved in the initial process that forms the lesions [45]. Neutrophil accumulation in gastric mucosa has been shown to induce microcirculatory abnormalities [46].…”
Section: Resultsmentioning
confidence: 99%
“…Several researchers have investigated the effects of many herbal medicines in protection against ethanol-induced gastric mucosal injuries by focusing on increases in the antioxidant defense system. Indeed, previous studies have demonstrated such increases with several herbal medicines, such as Argyreia speciosa, Orthosiphon stamineus, Pithecellobium jiringa, and propolis [5-8]. …”
Section: Introductionmentioning
confidence: 99%